Immobilized enzymes: a comprehensive review - Mohammad Rafiq Khan (SpringerOpen, 2021)
Abstract Background This article is a comprehensive review of the events recorded in the history of enzymology from twentieth century to the recent work of author’s groups on different biochemical aspects of the immobilized enzymes. The review differs from those presented before on the basis that it is not limited to one or few aspects. It extends its spectrum to a large number of aspects from the definition to biomedical applications of immobilized enzymes. Main body The author and his associates have proposed modification of classification of immobilized enzymes by Enzyme Engineering Conference 1971. His groups have worked on cell bound proteases of medicinal seeds and have given them the name of “naturally immobilized enzymes”. Thus, the author proposes that the enzymes may be basically classified into “naturally immobilized enzymes” and “artificially immobilized enzymes”. The artificially immobilized enzymes may be further sub-classified as done in 1971. Conclusion The classification suggested above sounds logical and thus acceptable to the author and his associates. The author and his associates also suggest some applications on the basis of their results on naturally immobilized enzymes.